The driving forces behind renewable energy consumption: A comprehensive analysis of key determinants and environmental concerns in ASEAN countries - Yusoff N.Y.M.; Aris H.; Nasiruddin W.H.M.; Rusli A.K.C.; Yurnaidi Z.; Safrina R.; Utama N.A.; Rosalia S.A. (Springer, 2025)
Renewable energy consumption is a crucial solution to addressing pressing environmental issues, particularly climate change and air pollution. Investigating the factors that drive its adoption is highly significant, as it provides policymakers and stakeholders with valuable insights to accelerate the transition to renewable energy sources. Through this approach, we can minimise the negative consequences of our reliance on fossil fuels, thereby protecting the integrity of the environment. Therefore, the primary goal of this study is to thoroughly investigate the main factors that influence renewable energy consumption and environmental change in six specifically chosen ASEAN countries. The stationarity of the 1990?2019 data was tested using panel data techniques such as Levin, Lin, and Chu (LLC), Im Pesaran (IPS), and the Shin W-stat test. According to the stationarity tests, after the first order, all variables exhibit stationarity. Additionally, Pedroni?s co-integration test result confirmed that there was a long-term relationship among the variables. Different methods, such as dynamic ordinary least squares (DOLS), fully modified ordinary least squares (FMOLS), and pooled ordinary least squares (POLS), are used for cointegration estimating. The results suggest that there is a positive co-integration between renewable energy use and GDP in six ASEAN countries, indicating a long-term relationship. The positive relationship between GDP and renewable energy use suggests that economic growth is the primary driving force behind ASEAN?s renewable energy adoption. However, factors like carbon emissions, population density, and foreign direct investment (FDI) negatively impact the demand for renewable energy. The limited availability of renewable energy in certain ASEAN countries may discourage foreign direct investment (FDI) due to the inverse relationship between FDI and renewable energy use. The studies also revealed that carbon emissions, which contribute to environmental pollution, do not motivate industries to invest in renewable energy. This finding would challenge the Environmental Kuznets Curve (EKC) hypothesis. According to the EKC, there is a significant transition towards renewable energy as a response to environmental degradation. However, it is worth noting that several ASEAN countries have experienced economic growth while also experiencing higher levels of carbon emissions. Given that economic expansion might not be environmentally beneficial, this research has implications for ASEAN energy policies. The ASEAN region faces a challenge in investing in renewable energy due to the excessive dependence on fossil fuels. Therefore, an in-depth evaluation of the main factor behind ASEAN?s environmental concerns, which promotes the adoption of renewable energy, can greatly influence policy decisions, particularly in attaining net zero emissions. Policymakers can utilise this comprehensive analysis to establish informed objectives for policies related to renewable energy and develop strategic plans, i.e. reforming fuel subsidies. The goal is to encourage the development of environmentally friendly and sustainable energy plans for the future in the ASEAN region. ? The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.